Analisis Dampak Pandemi Covid 19 Terhadap Ekonomi Negara Indonesia - Joy, Diandra; Sinaga, Enjelina; Adelia Parhusip, Feby; Nainggolan, Gaby Agustina; Rifai, Muhammad; Harahap, Nurul Febriyani; Tamba, Relly; Hery Cristian Gultom, Joshua (Sharia Journal and Education Center Publishing, 2024)
Abstract Since its appearance in December 2019 in Wuhan, China, the new variant of severe acute respiratory syndrome known as Covid-19 has immediately become a global concern. Its rapid spread has resulted in high death rates almost all over the world. All countries are struggling to stop the spread of this outbreak. In the context of international relations, the periodization in global politics is considered very important. This is usually marked by the occurrence of a major and important event that needs to be used as a milestone that divides the period of world politics in particular. The periodization is useful for understanding and interpreting the dynamics of international relations that occur within a certain period of time. So it is logical that the Covid-19 pandemic can be used as a new chapter in the periodization of global politics. The reasons are, first, all countries are greatly affected because of this pandemic. The type of research used in our title of Analysis of the impact of the covid 19 pandemic on the Indonesian state economy is descriptive qualitative research. Qualitative descriptive research is a problem formulation that guides research to explore or portray the social situation to be studied thoroughly, broadly and in depth. The type of qualitative descriptive data analysis technique is a research method that utilizes qualitative data and is described descriptively. This pandemic not only affects health, but also affects the economy, education, and social life in Indonesia. The economic impact of COVID-19 is felt in various sectors, including transportation, tourism, trade, health, and others. The pandemic has also caused a decrease in the number of foreign tourists visiting Indonesia, causing significant losses to the tourism industry. The pandemic has also had a significant impact on the education sector in Indonesia, with many schools and universities forced to close or operate remotely. The pandemic has also led to a decrease in the number of international students studying in Indonesia, causing significant losses to the education sector. Keywords: Covid-19, Economic Impact Abstrak Sejak kemunculannya pada Desember 2019 di Wuhan, Tiongkok, penyakit varian baru severe acute respiratory syndrome yang dikenal dengan Covid-19 langsung menjadi perhatian dunia. Daya persebarannya yang sangat cepat mengakibatkan tingginya tingkat kematian hampir di seluruh dunia. Semua negara berjuang agar bisa menghentikan meluasnya wabah ini. Dalam konteks ilmu hubungan internasional, pembabakan atau periodisasi dalam politik global dinilai sangat penting. Hal ini biasanya ditandai dengan terjadinya sebuah peristiwa besar dan penting sehingga perlu dijadikan sebagai tonggak yang membagi periode politik dunia secara khusus. Pembabakan tersebut berguna untuk memahami dan menafsirkan dinamika hubungan internasional yang terjadi dalam kurun waktu tertentu. Sehingga logis jika pandemi Covid-19 bisa dijadikan sebagai babak baru dalam periodisasi politik global. Alasannya adalah, pertama, semua negara sangat terpengaruh karena pandemi ini. Jenis penelitian yang digunakan dalam judul kami tentang Analisis dampak pandemi covid 19 terhadap ekonomi negara Indonesia adalah penelitian deskriptif kualitatif. Penelitian deskriptif kualitatif yaitu suatu rumusan masalah yang memandu penelitian untuk mengeksplorasi atau memotret situasi sosial yang akan diteliti secara menyeluruh, luas dan mendalam. Jenis teknik analisis data deskriptif kualitatif merupakan sebuah metode penelitian yang memanfaatkan data kualitatif dan dijabarkan secara deskriptif. Pandemi ini tidak hanya berdampak pada kesehatan, namun juga berdampak pada perekonomian, pendidikan, dan kehidupan sosial di Indonesia. Dampak ekonomi akibat COVID-19 dirasakan di berbagai sektor, antara lain transportasi, pariwisata, perdagangan, kesehatan, dan lain-lain. Pandemi juga menyebabkan penurunan jumlah wisatawan mancanegara yang berkunjung ke Indonesia sehingga menimbulkan kerugian yang signifikan bagi industri pariwisata. Pandemi ini juga berdampak signifikan pada sektor pendidikan di Indonesia, dengan banyak sekolah dan universitas terpaksa tutup atau beroperasi secara jarak jauh. Pandemi ini juga menyebabkan penurunan jumlah pelajar internasional yang belajar di Indonesia, sehingga menimbulkan kerugian yang signifikan bagi sektor pendidikan. Kata Kunci: Covid-19, Dampak Perekonomian